Végétation tardiglaciaire au Québec méridional et implications paléoclimatiques / Late-Glacial vegetation in Southern Québec and paleoclimatic implications - Richard, Pierre (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1977)
Recent pollen-analytical data allow a detailed reconstruction of the initial vegetation which followed the final retreat of the Wisconsinan ice sheet. The general scheme is the following. A period of periglacial desert was replaced more or less rapidly by tundra vegetation. Afforestation of the landscape proceeded either through a taïga phase, represented by a lichen — black spruce woodland, or by the establishment of an aspen parkland. Several postglacial vegetation types followed. The paleoclimatic interpretation of the data indicates severe climatic conditions around 11 400 BP at Mount Shefford, and around 7200 BP in the southern part of Laurentides Provincial Park. It has not yet been possible to show evidence for a climatic oscillation during the late-Glacial of Quebec, which appears very metachroneous. This metachroneity seems to be caused by the differences in altitude of the main physiographic regions and does not seem to correspond to the metachroneity in the ice retreat of the Wisconsinan ice sheet, view, there is now a firm basis to the statement that vegetation similar to the present-day tundra occupied a broad area in front of the ice sheet. Future research should define the duration and extension of the tundra on one hand, and on the other hand increase knowledge of its paleoclimatic significance.